Language Style Analysis of YouTube Streamer Windah Basudara in The Classroom Gameplay - Alya Raysha Davira; Otong Setiawan Djauhari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
In the digital era, a YouTuber plays a role not only in delivering content but also in creating a unique communication experience for their viewers. This study investigates the linguistic style of Windah Basudara during his gameplay of The Classroom a video that has become a popular talking point in the horror gaming community, particularly in April 2024. The game was selected because it successfully drew spontaneous and expressive reactions from the streamer, reflecting a high level of interaction in the comments section. The main focus lies in how Windah utilizes speech, greetings, humor, and spontaneous expressions to foster an emotional bond with his audience. Using a descriptive qualitative method and a light contextual pragmatic approach, this research classifies the types of linguistic style that emerge, without delving into overly complex linguistic theory. The results show that Windah’s communication strength lies in his ability to blend spontaneity, relatability, and a consistent personal style. These elements make his content feel lively and close to the viewers. The study concludes that a streamer’s success depends not only on the game played but also on their ability to connect naturally and entertainingly with their audience.